THE ROLE OF FOREIGN AFFAIRS ON FOREIGN POLICY FORMULATION IN AFRICA - Alier, Dr. Gabriel; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
The study sought to determine the role of Ministry of Foreign Affairs in Foreign  policy  formulation in South Sudan, the study was guided by three objectives which include: to identifying the strategy of formulate and implement foreign  policy, to examine the challenges facing foreign affairs  policy, to provide the best recommendations South Sudan foreign  policy  formulation. The researcher used both descriptive and analytical research designs. The researcher designs would be appropriate because data was analyzed using frequency counts and percentages that will be derive from the respondents it obtained through questionnaires and interview. The study contributed to the theoretical discussion of the decisions related to communication. This study also clarified that the Luhmannian system theory perspective is challenging and a complicated research line as the perspective is abstract and not backed up by empirical data. This helped streamline the focus of the dissertation and the aim of the research was moved from the lower level general decision making to strategic Ministry’s decision making and to the contribution towards formulating Foreign policy function. The study concluded that according to majority Ministry of Foreign Affairs employees had not yet adopted foreign policy strategies to promote Foreign policy. On the contrary, the majority of the Ministry of Foreign Affairs employees attested that the organization had adopted foreign policy strategies to promote Foreign policy. The researcher recommended that Ministry of Foreign Affairs management should review the policies and strategies guiding the implementation of foreign policy programs to incorporate them as an integral part of the management and communication function in order to enhance its impact on Foreign policy. The study also recommended that Ministry of Foreign Affairs management should address the bottlenecks hindering the implementation of foreign policy programs by adopting a hybrid approach of foreign policy strategies and tools to revitalize foreign policy function in promoting Foreign policy.